Integrated delivery of antiretroviral treatment and pre‐exposure prophylaxis to HIV‐1 serodiscordant couples in East Africa: a qualitative evaluation study in Uganda. Issue 5 (31st May 2018) - Ware, Norma C; Pisarski, Emily E; Nakku‐Joloba, Edith; Wyatt, Monique A; Muwonge, Timothy R; Turyameeba, Bosco; Asiimwe, Stephen B; Heffron, Renee A; Baeten, Jared M; Celum, Connie L; Katabira, Elly T
Abstract: Introduction: Serodiscordant couples are a priority population for delivery of new HIV prevention interventions in Africa. An integrated strategy of delivering time‐limited, oral pre‐exposure prophylaxis (PrEP) to uninfected partners in serodiscordant couples as a bridge to long‐term antiretroviral treatment (ART) for infected partners has been implemented in East Africa, nearly eliminating new infections. We conducted a qualitative evaluation of the integrated strategy in Uganda, to better understand its success. Methods: Data collection consisted of 274 in‐depth interviews with 93 participating couples, and 55 observations of clinical encounters between couples and healthcare providers. An inductive content analytic approach aimed at understanding and interpreting couples' experiences of the integrated strategy was used to examine the data. Analysis sought to characterize: (1) key aspects of services provided; (2) what the services meant to recipients; and (3) how couples managed the integrated strategy. Themes were identified in each domain, and represented as descriptive categories. Categories were grouped inductively into more general propositions based on shared content. Propositions were linked and interpreted to explain "why the integrated strategy worked." Results: Couples found "couples‐focused" services provided through the integrated strategy strengthened partnered relationships threatened by the discovery of serodiscordance. They saw in services hope for "getting help" to stay together, turned joint visits to clinic into opportunities for mutual support, and experienced counselling as bringing them closer together. Couples adopted a "couples orientation" to the integrated strategy, considering the health of partners as they made decisions about initiating ART or accepting PrEP, and devising joint approaches to adherence. A couples orientation to services, grounded in strengthened partnerships, may have translated to greater success in using antiretrovirals to prevent HIV transmission. Conclusions: Various strategies for delivering antiretrovirals for HIV prevention are being evaluated. Understanding how and why these strategies work will improve evaluation processes and strengthen implementation platforms. We highlight the role of service organization in shaping couples' experiences of and responses to ART and PrEP in the context of the integrated strategy. Organizing services to promote positive care experiences will strengthen delivery and contribute to positive outcomes as antiretrovirals for prevention are rolled out.